KAJIAN INTERNET MARKETING SEBAGAI MEDIA PEMASARAN PADA INDUSTRI PERBANKAN SYARIAH - Rodame Monitorir Napitupulu (Institut Agama Islam Negeri Padngsidimpuan, 2016)
AbstractThis paperwas areview about the development and applying internet marketing as a strategic tools to promote product and service of shariah banking industry. As we know, the internet user in the world was increased year to year. Shariah banking industry should utilize it to increase their customer. The method of this paper was literature study. The data was collected by observation, browsing and literature. The objective of this paper was to determine the application of internet marketing in shariah banking industry in order to inform, offer and promote product and service to potential customer. The result of this paper showed that many shariah banking in Indonesia has applied internet marketing as their marketing tool but yet optimized. It meant that the development of shariah banking industry pretty enaugh but still not as good as conventional bank in applying information technology. It become an opportunity as well as challenge to shariah banking industry to improve technology information in developing marketing of shariah banking industry in the future.Keyword : internet marketing, shariah banking, marketing